Violence against women in times of pandemic by covid-19 (Research, Society and Development, 2021)
This study aimed to describe information contained in scientific productions on violence against women in times of pandemic by covid-19. The chosen methodology was a bibliographic review of the integrative literature review type. To carry out this study, the following databases were consulted: MEDLINE, LILACS, SCIELO, Repositories and Academic Google. The Descriptors in Health Sciences (DeCS) were used in an associated way: “Woman”, “Violence”, “pandemic” and “Social Isolation”. After applying the inclusion criteria, 8 studies remained. With the included studies, critical and corroborative reviews were made about each one of them. Given the above, it is possible to think of the crisis started by the pandemic, of the social, economic and health order and the essential emergency measures adopted, but also of separation of resources that can help break the cycle of violence, which has increased the vulnerability of women.